Moods Pattern on Indonesian EFL University of Riau Kepulauan Studentsâ€™ Classroom Interaction - Ashari, Erwin; Shalehoddin, Shalehoddin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This study investigated, formulated and reasoned exchange structure used on Indonesian EFL university studentsâ€™ classroom interaction. Data transcriptions were taken from seven EFL classroom interaction videos between addressers and addressees, and field notes were taken to support primary data. Result shows that number of mood and residue reached 94.1 %and the rest was in elliptical moods . mood and residue domination was influenced by subject discussion and the formality of the situation matters. It was found that â€œmoveâ€ of exchange structure was in small number (three moves), so did elliptical clause. Since natural conversation was dominated by elliptical moods , long â€œmoveâ€ of exchange structure and elliptical clauses, thus, these could not be categorized as natural interaction. In line, Patterns of exchange structure coding contribute significantly toward EFL studentsâ€™ comprehension during classroom interaction.